Big Data in Healthcare: Possibilities and Challenges - A Systematic Literature Review - M. Barata, Luis; Louro, João; Afonso, João (Revista de Informática Teórica e Aplicada, 2025)
In today's world, the extensive use of Big Data emerges as a fundamental component in various sectors, and healthcare is no exception. This article explores the importance of using this data for the continuous improvement of patient care, providing them with a better quality of life. However, for this to happen, several challenges must be overcome, especially in data processing and analysis, and in this sector, it is crucial that their accuracy and integrity are not compromised, as they are related to life and death. In this study, we present a survey of technologies, possibilities, and challenges that arise in this field through a systematic review of various articles with cutting-edge approaches to the subject. Consequently, the advantages of using Big Data in healthcare will be highlighted, as well as the critical need to overcome the inherent challenges to achieve efficient and ethical implementation.